Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Profitabilitas terhadap Nilai Perusahaan - Samsu Anhari Faujianto Anhari; Wira Ganet Aribowo (JAMER : Jurnal Akuntansi Merdeka, 2022)
This study aims to determine the effect of investment decisions, funding decisions, and profitability partially on firm value in property, real estate, and building construction companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The research method in this study uses quantitative methods and is categorized into causal research. Samples were taken using a purposive sampling method based on certain criteria. The population in this study are property, real estate, and building construction companies listed on the Indonesia Stock Exchange for the 2016-2020 period. From a population of 76 firms, 30 companies were obtained as research samples. Analysis of the data in this study using Multiple Linear Regression Analysis using STATA 17 software. Based on the results of the analysis it was found that investment decisions have a positive and significant effect on firm value. Funding decisions have a negative and significant effect on firm value. While the profitability variable does not affect firm value.